UMP covets 7 medals, Best Booth at MTE 2010 - UMP, PNC
Universiti Malaysia Pahang (UMP) coveted two gold, two silver and three bronze medals at the 9th Malaysia Technology Expo (MTE 2010) held at the Putra World Trade Centre on February 4-6 recently.